Occult-Related Crime and the Policing thereof, through the lens of Cosmology of Socio-Political Factors - Scholtz, Marcia (Department of Public Law, 2023)
Occult-related crimes are crimes of a spiritual nature, in Africa, the study of these crimes could be approached from the field of African cosmology, which encompasses spirituality, culture, and nature. But these crimes also exist in a sociopolitical context, as well as an economic one. It is said that modern occult crimes have become entrepreneurial, this is what the Comaroffs (1999) call ‘modern occult economies.' The transition from traditional occult practices to modern practices can further be explored through a lens of, deeply rooted belief systems, being hijacked and manipulated by the opportunistic. This research explores not only traditional African occult crime, but also the Western branch practices and hybrid systems, and it touches on global occult crimes and ‘moral panics'. Occult crime is not labelled as such, but as general crimes, but the argument is for the typology of occult crime, for this has implications on police training and investigation, as well sentencing processes in courts. Modern-day panics are described as conspiracy theories, and in the 80s and 90s a significant example of this phenomenon was labelled the ‘Satanic Panic', and more recently, it could be argued in the theories of groups like QAnon. Further, the policing of the occult is engaged, specifically in South Africa, through exploring the challenges in the policing of occult crimes, by general police officers and South Africa's Occult Related Crime Unit (ORCU). Complexities in the South African criminal justice system and the occult, as with legislation and the judiciary, is an ongoing conversation between scholars, and one this research also touches on.